ALGORITHMIC PROCEDURES OF SYNTHESIS OF VARIABLE STRUCTURE SYSTEMS FOR MARINE VEHICLES CONTROL - Timchenko, V. L.; Lebedev, D. O. (Radio Electronics, Computer Science, Control, 2018)
Context. Algorithmic procedures for synthesizing optimal speed systems with variable feedback structure and a given dimension of the vehicle model, required type of stabilization trajectories and constraints on control actions are proposed for solving the tasks of increasing level of automatization control processes of marine vehicles at maneuvering and dynamic positioning. The study object are dynamic processes which stabilize marine mobile objects in conditions of incomplete informative nature of their models and the environment. The subject of the research is automated algorithmic procedures for synthesis of optimal control systems with variable feedback structure. Objective – to increase the level of automation and quality indicators for the control processes of marine mobile objects on the basis of creating automated procedures for the synthesis of robust-optimal systems. Method. To optimize control processes, optimal stabilization trajectories are formed, also the necessary switching moments and the type of control functions are determined for the feed-backs of optimizing control processes. Nonlinear models of marine vehicles with incomplete informativeness of model parameters and external disturbances are considered. The robust correcting control circuit providing compensation of the errors of the actual trajectory of physical object from the optimal trajectories, which arise from a mismatch between the parameters of the model and the physical object and from the effect of uncontrolled disturbances, is proposed. Thus, the control system is invariant for incomplete informativeness of models and minimal values errors of control can be achieved. Results. The algorithmic procedures for synthesizing robust optimal systems of variable structure have been implemented and studied in the simulation of the stabilizing process of a mobile marine object on a given trajectory, the results of which confirmed the correctness and effectiveness of the proposed approach. Conclusions. On the basis of systems with variable feedback structure for the criterion of optimality for the maximum operating speed, algorithmic procedures for the automated synthesis of control functions for multidimensional nonlinear systems describing the dynamics of mobile marine objects have been developed. The software tools for automating the synthesis process and schematic solutions of control systems are practically applicable for a wide class of mobile objects of various technical purposes.